First Record of the Ladder Gudgeon Bostrychus scalaris Larson, 2008 (Gobiiformes: Eleotridae: Butinae) from Mangrove Estuary of South Sumatra, Indonesia - Rusdianto, Rusdianto; Wahyudewantoro, Gema; Wibowo, Kunto (Universitas Gadjah Mada, 2024)
A single specimen of Bostrychus scalaris was collected from the mangrove estuary of Banyuasin Regency, South Sumatra, Indonesia. The species was originally described as a new species based on a single specimen collected from the disturbed mangrove site in Sementa River, Selangor State, Malaysia. Subsequently, the species was known to have been distributed in Singapore based on a watercolour painting by a French naturalist also in Mekong River in Soc Trang Province, Vietnam. The present specimen of B. scalaris represents the first record of the species from Indonesian water and southernmost record of the species.